2016
DOI: 10.5005/jp-journals-10024-1970
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Shear Bond Strength and Microleakage of Various Bulk-fill Bioactive Dentin substitutes: An in vitro Study

Abstract: Introduction:Various bulk-fill materials depending on their composition, viscosity, and flow ability have different physical and mechanical properties. The aim of this in vitro study was to determine and compare the shear bond strength and microleakage properties of activa restorative with other bulk-fill restorative materials surefil (SDR), Biodentine, ever X posterior. Materials and methods:Forty permanent premolars were selected for shear bond strength, and 20 permanent premolars were selected with class II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…concluded that SFRC restorations in class V cavities showed an improved marginal integrity when compared to the conventional PFC resin restorations . However, some other authors reported no certain effect of SFRC on microleakage and marginal adaptation of composite resin restorations …”
Section: Resultssupporting
confidence: 59%
“…concluded that SFRC restorations in class V cavities showed an improved marginal integrity when compared to the conventional PFC resin restorations . However, some other authors reported no certain effect of SFRC on microleakage and marginal adaptation of composite resin restorations …”
Section: Resultssupporting
confidence: 59%
“…In addition, they also contain a bioactive ionic resin matrix, and thereby are able to achieve polymerization by both light cure and chemical cure. [10][11][12][13][14][15][16][17][18][19][20][21] Thus, there are three hardening mechanisms involved with the Activa restorative, and release and recharge with calcium, phosphate, and more fluoride ions than glass ionomers. In addition, Activa contains no bisphenol A (BPA), bisphenol A glycidyl methacrylate (bis-GMA), or BPA derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…They are free from bisphenol A derivatives. [10,11] The aim of this in vitro study was to determine and compare the shear bond strength of activa bioactive restorative with and without adhesive and nano-composite.…”
Section: Introductionmentioning
confidence: 99%
“…"White line" margins, which are considered typical of freshly finished bonded resin bonded composite restorations, are prominently absent, which is most likely owing to low polymerization shrinkage. (23) Contradictory results in previous study that have employed similar techniques for the same material have often provided. This contrast may have resulted from different handling and manipulation of materials.…”
Section: Dentalmentioning
confidence: 98%
“…The results agreed with those reported in previous studies. (15,23) This might be attributed to Activa Restorative contains glass particles and polyacid components of resin-modifed glass ionomer cements, which undergo the acid/base hardening reaction of all glass-ionomer systems. Also, the ionic resin component which contains phosphate acid groups with antimicrobial properties that improve the interaction between the resin and the reactive glass fillers and enhance the interaction with tooth structure.…”
Section: Dentalmentioning
confidence: 99%